PENGARUH LITERASI KEUANGAN, GAYA HIDUP DAN DIGITAL PAYMENT TERHADAP PERILAKU KONSUMTIF GENERASI Z - Nurul Septiyani; Besse Wediawati; Agus Solikhin (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
This study aims to analyze the influence of financial literacy, lifestyle, and the use of digital payment on the consumptive behavior of Generation Z. The object of this research is undergraduate students of the Faculty of Economics and Business at Jambi University from the 2021–2024 cohorts. The study employs a quantitative approach using the Partial Least Square (PLS) method with the assistance of SmartPLS 4 software. Primary data were collected through a questionnaire using a 5-point Likert scale and distributed via Google Form. A total of 100 respondents were selected using the Slovin formula from a population of 3,131 students. The results show that: (1) financial literacy has a negative and significant effect on consumptive behavior; (2) lifestyle has a positive and significant effect on consumptive behavior; and (3) digital payment also has a positive and significant effect on consumptive behavior. These findings imply that improving financial literacy can reduce consumptive behavior, whereas a consumptive lifestyle and the ease of digital payment tend to increase such behavior.